2015
DOI: 10.1097/gme.0000000000000557
|View full text |Cite
|
Sign up to set email alerts
|

Use of a levonorgestrel-containing intrauterine system with supplemental estrogen improves symptoms in perimenopausal women

Abstract: A brief, low-dose estrogen intervention, combined with a LNG-IUS, led to significant improvement of some common perimenopausal symptoms. Such a "minimalist" approach to management of the perimenopause holds promise for reducing common, bothersome perimenopausal symptoms while maintaining effective contraception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…The use of oral or percutaneous estrogen therapy (ET) together with LNG-IUS is not only effective for alleviating the symptoms of menopause but also for preventing endometrial hyperplasia. Even in the case of a normal menstrual cycle, if the symptoms of menopause are severe, the use of a combination therapy of low-dose percutaneous estrogen and LNG-IUS could effectively control a hot flush [8]. In addition, some reports have shown that it could help improve symptoms that appear during menopausal transition such as depression, reduced quality of sleep, and increased anxiety [9,10].…”
Section: Mht For Women In Menopausal Transitionmentioning
confidence: 99%
“…The use of oral or percutaneous estrogen therapy (ET) together with LNG-IUS is not only effective for alleviating the symptoms of menopause but also for preventing endometrial hyperplasia. Even in the case of a normal menstrual cycle, if the symptoms of menopause are severe, the use of a combination therapy of low-dose percutaneous estrogen and LNG-IUS could effectively control a hot flush [8]. In addition, some reports have shown that it could help improve symptoms that appear during menopausal transition such as depression, reduced quality of sleep, and increased anxiety [9,10].…”
Section: Mht For Women In Menopausal Transitionmentioning
confidence: 99%
“…Women with perimenopausal complaints, using LNG-IUS, can start estrogen therapy as the LNG-IUS will protect the endometrium. 88 …”
Section: Discussionmentioning
confidence: 99%
“…In the presence of the uterus, maximum reduction of risk can only be achieved by eliminating exposure of circulating progestin or progesterone at the breast. The placement of a low‐dose levonorgestrel eluting intrauterine device (IUD) is the best solution to this problem . The local release of progestin prevents endometrial proliferation and, in the newer smaller devices, yields systemic progestin circulating levels in low picogram concentrations—orders of magnitude less than nanogram concentrations associated with oral MPA (2.5 mg) .…”
Section: Opportunitymentioning
confidence: 99%